Polemik Fungsi Sosial Tanah dan Hak Menguasai Negara Pasca UU Nomor 12 Tahun 2012 dan Putusan Mahkamah Konstitusi Nomor 50/PUU-X/2012 - King Faisal Sulaiman (The Constitutional Court of the Republic of Indonesia, 2021)
This study examines, Firstly, aspects of the formation of Law Num. 2/2012. Secondly, interpretation of the meaning of development in the public interest. Thirdly, the compensation process for the release of land rights for development. Finally, polemic of MK's Decision Num. 50/PUU-X/2012. The findings show, procedural aspects of the formation of Law Num. 2/2012, is not in accordance with the rules for the formation of applicable laws. Likewise, the meaning conception of the public interest and the process of compensation for land is still far from the spirit of the Law Num. 5 of 1960 (UUPA) Jo Article 33 of the 1945 Constitution. The Post of MK's Decision Num. 50/PUU-X/2012, there needs to be a legislative review of Law Num. 2/2012, to deconstruct the meaning of “social function of the land” to conform to the philosophy of Article 33 of the 1945 Constitution and the Law Num. 5 of 1960 (UUPA). The Parliament must immediately complete the Agrarian Structure Renewal and Arrangement Bill, the Agrarian Conflict Resolution Bill, and the Natural Resource Management Bill, as mandated by MPR Decree Num. IX/2001 Jo Tap MPR Num. V/2003. Development in the public interest, must be placed in the spirit of social and agrarian reform in order to achieve maximum prosperity for the people.